Pengaruh Motivasi Dan Pengalaman Kerja Terhadap Kinerja Karyawan Pada Yayasan Rumah Pagi Bahagia Tangerang Selatan - Amanda Putri, Merlinda; Tilova, Nurdinni (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the influence of Motivation and Work Experience on Employee Performance at Yayasan Rumah Pagi Bahagia. This research uses a quantitative method. The population in this study consists of all employees totaling 57 individuals. The sampling technique uses a quantitative approach. The data analysis methods include instrument testing, classical assumption testing, simple and multiple linear regression analysis, as well as hypothesis testing. The t-test results show that the Motivation variable has a t-value of 6.153 > t-table 2.004 with a significance value of 0.000 < 0.05, indicating that Motivation has a partial effect on Employee Performance. The Work Experience variable has a t-value of 10.101 > t-table 2.004 with a significance value of 0.000 < 0.05, which means that Work Experience also has a partial effect on Employee Performance. The F-test results show that the F-count is 55.781 > F-table 3.17 with a significance value of 0.000 < 0.05, indicating that Motivation and Work Experience simultaneously have a positive and significant effect on Employee Performance. The coefficient of determination (R Square) is 0.674, which means that Motivation and Work Experience jointly influence Employee Performance by 67.4%, while the remaining 32.6% is influenced by other variables not examined in this study